Identification of phosphorylation sites in the COOH‐terminal tail of the μ‐opioid receptor. (30th November 2012) - Chen, Ying‐Ju; Oldfield, Sue; Butcher, Adrian J.; Tobin, Andrew B.; Saxena, Kunal; Gurevich, Vsevolod V.; Benovic, Jeffrey L.; Henderson, Graeme; Kelly, Eamonn
Abstract Phosphorylation is considered a key event in the signalling and regulation of the μ opioid receptor (MOPr). Here, we used mass spectroscopy to determine the phosphorylation status of the C‐terminal tail of the rat MOPr expressed in human embryonic kidney 293 (HEK‐293) cells. Under basal conditions, MOPr is phosphorylated on Ser363 and Thr370, while in the presence of morphine or [D‐Ala2, NMe‐Phe4, Gly‐ol5]‐enkephalin (DAMGO), the COOH terminus is phosphorylated at three additional residues, Ser356, Thr357 and Ser375. Using N‐terminal glutathione S transferase (GST) fusion proteins of the cytoplasmic, C‐terminal tail of MOPr and point mutations of the same, we show that, in vitro, purified G protein‐coupled receptor kinase 2 (GRK2) phosphorylates Ser375, protein kinase C (PKC) phosphorylates Ser363, while CaMKII phosphorylates Thr370. Phosphorylation of the GST fusion protein of the C‐terminal tail of MOPr enhanced its ability to bind arrestin‐2 and ‐3. Hence, our study identifies both the basal and agonist‐stimulated phospho‐acceptor sites in the C‐terminal tail of MOPr, and suggests that the receptor is subject to phosphorylation and hence regulation by multiple protein kinases.